Human remains under the microscope of funerary taphonomy: Investigating the histological biography of the decaying body in the prehistoric Aegean. (December 2020) - Papakonstantinou, Niki; Booth, Thomas; Triantaphyllou, Sevasti
Highlights: Variation in diagenetic patterns across Aegean prehistoric sites and mortuary loci. The extent of bioerosion is more likely associated with early taphonomic processes. High levels of bioerosion in Neolithic samples suggest primary soil burial of bodies. Bone assemblages from Minoan sites show evidence for variable taphonomic histories. Bodies deposited in Mycenaean tombs were rapidly skeletonized by invertebrates. Abstract: Funerary practices and especially the manipulation of the dead body have in the last decades become a central focus in prehistoric Aegean mortuary research. Variation in the character of human remains recovered from a rich array of mortuary contexts in varying state of articulation suggests that the dead were subject to a diverse range of mortuary rites. Taphonomic analysis of skeletal remains has been more recently employed by bioarchaeological research in the prehistoric Aegean with a view to understanding modes of pre- and post-burial treatment and reconstructing funerary activities. Recent studies of modern and archaeological bone have shown that bacterial bioerosion of internal bone microstructures is related to taphonomic processes which affect soft tissue decomposition and thus varies in ways which correspond to early post mortem funerary and corpse treatment. This paper presents the histotaphonomic analysis by thin section light microscopy of 108 human bones (107 individuals) from eleven Aegean human skeletal assemblages dating from the Neolithic to the Late Bronze Age. The results show variation in bacterial attack in different burial environments and often in the same deposit, which is more likely to reflect early taphonomic processes rather local soil circumstances. The microscopic analysis is combined with macroscopic (taphonomic surface modifications) and contextual information to discriminate between different formation mechanisms of skeletal assemblages and make inferences about funerary treatment and manipulation of the deceased. High levels of bacterial attack in Neolithic articulated and disarticulated samples suggest primary soil burial soon after death. Minoan bone assemblages provide evidence of considerable variation in levels of diagenesis, suggesting divergent taphonomic histories, whereas the results from Mycenaean sites are consistent with the deposition of fresh, intact bodies in chamber tombs, resulting in rapid skeletonisation by invertebrates and limited bone exposure to bacteria associated with soft tissue decomposition.